Influence of Product Quality, Store Atmosphere, and Price Fairness on Repurchase Intention among Mixue Progo Customers in Pekalongan City - Nofita Salsabila; Rif’ah Dwi Astuti; Taviyastuti (Admisi dan Bisnis, 2026)
This research is motivated by a noticeable decline in sales at Mixue Progo, which is presumed to stem from a reduced intention among customers to repurchase. The purpose of this study is to analyze the impact of product quality, store atmosphere, and fair pricing on the repurchase intention of Mixue Progo consumers in Pekalongan City. A quantitative research method was adopted through a survey approach, involving 175 respondents selected via purposive sampling. Out of the total, 160 valid responses were processed and analyzed using multiple linear regression with the help of SPSS version 23. The findings reveal that product quality, store ambiance, and price fairness each exert a significant and positive influence—both separately and collectively—on repurchase intention. These outcomes suggest that enhancing product standards, maintaining an inviting store environment, and ensuring fair pricing strategies are key to encouraging repeat purchases. Moreover, the study reinforces the Expectation Confirmation Theory (ECT), which posits that repurchase intentions emerge when consumers perceive that the performance of a product or service meets or surpasses their initial expectations.